Intraocular sarcoidosis: association of clinical characteristics of uveitis with findings from 18F-labelled fluorodeoxyglucose positron emission tomography. Issue 1 (3rd April 2011) - Rahmi, Ahmed; Deshayes, Emmanuel; Maucort-Boulch, Delphine; Varron, Loig; Grange, Jean Daniel; Kodjikian, Laurent; Seve, Pascal
Abstract : Aims: To assess specific clinical criteria in patients with uveitis that are related to signs of sarcoidosis on 18 F-labelled fluorodeoxyglucose positron emission tomography ( 18 F-FDG-PET). Methods: Retrospective study of 54 consecutive patients with chronic uveitis for whom a PET scan was done because of suspected sarcoidosis, between July 2004 and December 2009. All the patients underwent a clinical examination, biological tests and a high-resolution CT of the chest. Results: 17 of the 54 patients (31.5%) presented hypermetabolic foci on 18 F-FDG-PET scan consistent with sarcoidosis. Among them eight patients (14.8%) underwent biopsy showing non-caseating granuloma. At the end of the study, 10 patients (18.5%) were considered as having a presumed sarcoidosis and seven patients (12.9%) as having indeterminate sarcoidosis. The increasing age at the diagnosis of uveitis (p=0.01), the presence of posterior synechiae (p=0.01) and a positive high-resolution CT of the chest (p=0.01) were significantly related to an abnormal PET scan. Conclusions: Increasing age at the diagnosis of uveitis, the presence of posterior synechiae and the positivity of high-resolution chest CT are associated with 18 F-FDG PET scan signs consistent with sarcoidosis.